Influence of tara gum and xanthan gum on rheological and textural properties of starch-based gluten-free dough and bread - Vidaurre-Ruiz, J (2019)
The aim of this research was to determine the influence of tara gum and xanthan gum on rheological and textural properties of gluten-free doughs and breads made from corn starch and potato starch. Four formulations were developed: corn starch with xanthan gum (CS-XG), corn starch with tara gum (CS-TG), potato starch with xanthan gum (PS-XG) and potato starch with tara gum (PS-TG) (XG and TG—0.5% of flour). Rheological and textural properties of doughs were evaluated, as well as specific volume, alveolar structure and texture profile of breads. The results showed that the addition of tara gum increased pasting properties of the potato starch formulation, however, in the corn starch formulations, it was not significantly different from xanthan gum addition. All formulations showed more elastic than viscous behavior (G′>G″) and these viscoelastic properties had an influence on the kinetics of dough growth during the leavening process. The formulation PS-XG presented high specific volume, low crumb hardness, and good crumb structure, while the PS-TG showed inferior properties. In contrast, in the corn starch formulations, CS-XG and CS-TG presented very similar physical characteristics. The application of tara gum in gluten-free breads is reported for the first time and depending on the starch used it showed desirable properties for obtaining good quality products.